ADVANTAGES OF ELECTRONIC EDUCATIONAL LITERATURE - Kurbanova, Muxabbat (Журнал иностранных языков и лингвистики, 2023)
In our article, the electronic textbooks and encyclopedias currently used in the educational system are used by ordinary people, and specialists, book publishers, programmers, magazine journalists, and advanced teachers are actively involved in the creation of such publications, electronic and encyclopedias guides and general concepts. The methods of their use in the educational process are also considered by teachers of various disciplines.